Implementation of administrative service policy at the Makassar city population and civil registry service - Sumardi, Sumardi; Nawi, Rusdin (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The problem in this study is that implementing policies at the Makassar City Population and Civil Registry Office could be more optimal. This study aims to analyze the implementation of administrative service policies at the Makassar City Population and Civil Registry Office. This type of research is qualitative research. Primary data sources were obtained through interviews with 18 informants and supported by observation and documentation review at the Makassar City Population and Civil Registry Office. Data collection techniques in this study used interviews, observations, and documentation review. The results showed that implementing administrative service policies had interpreted the above policies. However, the employee placement arrangement could be more effective because it only places two employees at the file verification counter, so its implementation results in long queues. This shows a need for coordination by implementers of existing service arrangements and procedures and a lack of socialization in the community, resulting in a weak ability to adapt to the procedures and service innovations that have been carried out.